2016
DOI: 10.1111/aab.12303
|View full text |Cite
|
Sign up to set email alerts
|

The red imported fire ant, Solenopsis invicta, modifies predation at the soil surface and in cotton foliage

Abstract: Red imported fire ants, Solenopsis invicta, are generalist predators that can have major impacts on foliar arthropod communities in agricultural systems; however, their effects as predators at the soil surface have not been adequately characterized. We examined the contribution of fire ants to predation at the soil surface and in cotton foliage at two sites and over the course of two field seasons in Georgia, using egg masses of the beet armyworm, Spodoptera exigua. To assess interactions between fire ants and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Red imported fire ants also congregate around uninsulated electrical equipment, causing short circuits and interfering with regular switch operation, damaging agricultural machinery and equipment, and interfering with manual operation [10,11]. Red imported fire ants cause enormous economic harm, costing the United States more than USD 6 billion per year in damage restoration, medical care, and control measures [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Red imported fire ants also congregate around uninsulated electrical equipment, causing short circuits and interfering with regular switch operation, damaging agricultural machinery and equipment, and interfering with manual operation [10,11]. Red imported fire ants cause enormous economic harm, costing the United States more than USD 6 billion per year in damage restoration, medical care, and control measures [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently RIFA quickly spread to the neighboring Caribbean islands, and then Australia, New Zealand, Japan, and South Korea (Sung et al 2018;Wylie et al 2016;Zhang et al 2007). RIFA has the potential to establish successfully around the world due to its strong adaptive and reproductive capabilities (Bertelsmeier et al 2017;Wickings & Ruberson 2016), resulting in possibly huge economic losses and environmental and social damage (Ross & Shoemaker 2008;Williams et al 2001). In the United States alone, control, medical treatment, and damage losses from RIFA have been estimated at almost US$6 billion per year (Ascunce et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…RIFA has the potential to establish successfully around the world due to its strong adaptive and reproductive capabilities (Bertelsmeier et al . 2017; Wickings & Ruberson 2016), resulting in possibly huge economic losses and environmental and social damage (Ross & Shoemaker 2008; Williams et al . 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In Alabama, Georgia, and Texas, the predation potential of agronomic pests by S. invicta in agroecosystems has been reported especially on various stages of lepidopteran pests (Ruberson et al 1994;Diaz et al 2004;Styrsky & Eubanks 2010;Wickings & Ruberson 2016). Foraging individuals on plant canopies of cotton (Gossypium hirsutum L.; Malvaceae) and peanut (Arachis hypogaea L.; Fabaceae) have played a role as predators by removing the eggs of Helicoverpa zea (Boddie) (Lepidoptera: Noctuidae) (Diaz et al 2004;Wickings & Ruberson 2016). A previous report by Diaz et al (2004) also indicated that early in the cotton season, S. invicta populations are attracted to the honeydew produced by aphid populations.…”
Section: Introductionmentioning
confidence: 99%